2019
DOI: 10.3390/antiox8070205
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Ultrasound-Assisted Extraction of Polyphenols from Myrtus communis L. Pericarp

Abstract: Response surface methodology (RSM) was used to optimize the extraction of phenolics from pericap of Myrtus communis using ultrasound-assisted extraction (UAE). The results were compared with those obtained by microwave-assisted extraction (MAE) and conventional solvent extraction (CSE) methods. The individual compounds of the optimized extract obtained by UAE were identified by ultra-high-performance liquid chromatography coupled with diode array detection and electrospray ionization mass spectrometry (UHPLC-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 54 publications
(94 reference statements)
2
24
0
Order By: Relevance
“…The results demonstrated that ethanol concentration, irradiation time, liquid solvent-to-solid ratio and amplitude affected significantly the yield of total polyphenolic content [41]. The optimal conditions for the isolation of M. communis polyphenolic extract using UAE were 70% v/v ethanol concentration, 7.5 min irradiation time and 30% liquid solvent-to-solid ratio [41]. In addition, isolation of M. communis polyphenolic extract using UAE was more efficient than MAE and conventional solvent extraction methods [41].…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…The results demonstrated that ethanol concentration, irradiation time, liquid solvent-to-solid ratio and amplitude affected significantly the yield of total polyphenolic content [41]. The optimal conditions for the isolation of M. communis polyphenolic extract using UAE were 70% v/v ethanol concentration, 7.5 min irradiation time and 30% liquid solvent-to-solid ratio [41]. In addition, isolation of M. communis polyphenolic extract using UAE was more efficient than MAE and conventional solvent extraction methods [41].…”
mentioning
confidence: 97%
“…The main polyphenols found in the extract were rutin, epigallocatechin, ferulic acid, and quercetin [40]. Bouaoudia-Madi et al [41] have also used UAE to isolate polyphenolic extracts from Myrtus communis L. pericarp, a plant native of the Mediterranean basin. The results demonstrated that ethanol concentration, irradiation time, liquid solvent-to-solid ratio and amplitude affected significantly the yield of total polyphenolic content [41].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis was performed in an Ultimate 3000 (Dionex Co., San Jose, CA, USA) apparatus equipped with an ultimate 3000 Diode Array Detector (Dionex Co., San Jose, CA, USA) and coupled to a mass spectrometer, following the general procedure previously described [50]. Samples (5 mg/mL) were prepared in ethanol and analyzed through the injection of 2 µL.…”
Section: Uhplc-esi-dad-ms N Analysismentioning
confidence: 99%